The importance of Halal in Islamic law and Muslim life : fundamental principles and cardinal values pertaining to human welfare - Mohd. Noor, Fauziah (TM-Info-Media Sdn. Bhd., 2009)
Islamic law consists of five main legal rulings (hukm) namely obligatory (wajib), prohibited (haram),recommended (mandub), reprehensible (makruh) and permissible (mubah). Indeed, the legal rulings which governed Muslims' lives were intended to achieve the objectives of Shari'ah (maqasid as-Shari'ah). The objectives of the Islamic law consists of the protection of religion, protection of life, protection of mind, protection of lineage and protection ". of property. Thus, the Maqasid as-Shari'ah has been an important tool for formulating the fundamental principles cardinal values pertaining human welfare.